Evolution of Elastic and Mechanical Properties During Fault Shear: The Roles of Clay Content, Fabric Development, and Porosity. Issue 3 (21st March 2020) - Kenigsberg, Abby R.; Rivière, Jacques; Marone, Chris; Saffer, Demian M.
Abstract: Phyllosilicates weaken faults due to the formation of shear fabrics. Although the impacts of clay abundance and fabric on frictional strength, sliding stability, and porosity of faults are well studied, their influence on elastic properties is less known, though they are key factors for fault stiffness. We document the role that fabric and consolidation play in elastic properties and show that smectite content is the most important factor determining whether fabric or porosity controls the elastic response of faults. We conducted a suite of shear experiments on synthetic smectite‐quartz fault gouges (10–100 wt% smectite) and sediment incoming to the Sumatra subduction zone. We monitored Vp, Vs, friction, porosity, shear and bulk moduli. We find that mechanical and elastic properties for gouges with abundant smectite are almost entirely controlled by fabric formation (decreasing mechanical and elastic properties with shear). Though fabrics control the elastic response of smectite‐poor gouges over intermediate shear strains, porosity is the primary control throughout the majority of shearing. Elastic properties vary systematically with smectite content: High smectite gouges have values of Vp  ~ 1, 300–1, 800 m/s, Vs  ~ 900–1, 100 m/s, K  ~ 1–4 GPa, and G  ~ 1–2 GPa, and low smectite gouges have values of Vp  ~ 2, 300–2, 500 m/s, Vs  ~ 1, 200–1, 300 m/s, K  ~ 5–8 GPa, and G  ~ 2.5–3 GPa. We find that, even in smectite‐poor gouges, shear fabric also affects stiffness and elastic moduli, implying that while smectite abundance plays a clear role in controlling gouge properties, other fine‐grained and platy clay minerals may produce similar behavior through their control on the development of fabrics and thin shear surfaces. Key Points: Due to grain size and enhanced fabric formation, smectite content within gouge acts as a primary control on evolution of elastic properties during shear Mechanical and elastic properties of smectite‐rich gouges are controlled by fabric; those of smectite‐poor gouge are controlled by porosity Shear fabric formation causes transient reduction in ultrasonic velocities and elastic moduli even as porosity decreases